DEKADENSI MORAL PEBISNIS - Sakinah Sakinah (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2008)
Business realm is a field that promise the doer a large profit. Even so, it is commonly recognized that most of business persons commit the dishonest and unfair actions. They are even careless of norm-ethic and business regulation to gain an utmost profit but provide smallest amount capital. This secular concept emerges counterfeit or fake such as unauthorized copying, reproduction, hiring, lending etc. The act of fake could be indentified in the following cases, counterfeiting cosmetic products, medical-traditional herbs mixing with white cement, illegal expiring food, gelatinized milk. These gives negative impact to the costumers economically and healthily. Then, this article is about to discuss the moral decadence of business person, Islamic view on business, business ethic, the essence of illegal transaction in order to avoid a prohibited syara’. It includes al-akl bi al-bâthil, ribâ, gharar , al-Quran terminologies, to explain an illegal business that it is an action ofstripping anyone else’s rights by consuming an authorized (haram)things.